2010
DOI: 10.1097/pgp.0b013e3181e2e8ee
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ploidy Heterogeneity in Endometrial Carcinoma

Abstract: DNA ploidy has been reported to be a prognostic marker for patients with endometrial carcinoma. In this study, DNA ploidy and histologic heterogeneity were evaluated by comparing curettage and hysterectomy specimens in 99 consecutive patients diagnosed with endometrial carcinoma. High-resolution DNA ploidy image analysis and review of histologic specimens were performed. The histologic subtypes were identical in 77 (78%) and differed in 22 (22%) cases. The DNA ploidy results were concordant in the curettage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Subsequently, after terminating the study, we found that the DNA ploidy results differed in the specimens in approximately one-fourth of the cases [30]. We found that DNA ploidy results from hysterectomy specimen provided better prognostic information compared with curettage specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, after terminating the study, we found that the DNA ploidy results differed in the specimens in approximately one-fourth of the cases [30]. We found that DNA ploidy results from hysterectomy specimen provided better prognostic information compared with curettage specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, DNA ploidy was analyzed either preoperatively or on hysterectomy specimens and with different methods (see Methods). However, the concordance between DNA ploidy on curettage and hysterectomy specimens is considered to be fairly high . The majority of DNA analyses were performed by flow cytometry on deparaffinized tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, these somatic copy number alterations may not be homogeneous across the tumor as demonstrated by intratumoral heterogeneity of DNA ploidy, a surrogate for copy number alterations. 34 Consequently, nuclear grade may also vary.…”
Section: Serous Molecular Type With Areas Resembling Other Endometriamentioning
confidence: 99%